2017
DOI: 10.1111/bjh.14652
|View full text |Cite
|
Sign up to set email alerts
|

Increased non‐relapse mortality due to high‐dose cytarabine plus CY/TBI in BMT/PBSCT for acute lymphoblastic leukaemia in adults

Abstract: The efficacy of high-dose cytarabine (HDCA) plus cyclophosphamide/total-body irradiation (CY/TBI) has been proved in cord blood transplantation (CBT) for acute lymphoblastic leukaemia (ALL), but not in bone marrow or peripheral blood stem cell transplantation (BMT/PBSCT). In this cohort study, we compared the prognosis of CY/TBI (N = 1244) and HDCA/CY/TBI (N = 316) regimens in BMT/PBSCT for ALL. The addition of HDCA decreased post-transplant relapse, while significantly increasing non-relapse mortality (risk r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Retrospective analysis of Japanese registry data showed that HDCA/CY/TBI improved prognosis in CBT, but had no effectiveness due to increased NRM in BMT/PBSCT. 28,29 In this study, the benefit of VP16/CY/TBI was less apparent in CBT than in BMT/PBSCT, although the number of cases was smaller in CBT.…”
Section: No Survival Advantage With Vp16/cy/tbi Observed In Patients ...mentioning
confidence: 58%
“…Retrospective analysis of Japanese registry data showed that HDCA/CY/TBI improved prognosis in CBT, but had no effectiveness due to increased NRM in BMT/PBSCT. 28,29 In this study, the benefit of VP16/CY/TBI was less apparent in CBT than in BMT/PBSCT, although the number of cases was smaller in CBT.…”
Section: No Survival Advantage With Vp16/cy/tbi Observed In Patients ...mentioning
confidence: 58%
“…It is well recognised that simple conditioning intensification by the additional use of chemotherapeutic agents usually results in the reduction of relapse and increase of NRM simultaneously; ultimately, OS after intensified conditioning is similar to that after standard regimen. 38–40 However, superior OS is observed in some retrospective studies if the clinical study is conducted by inclusion of mainly young and fit patients. 17 41 In BM transplantation and peripheral blood stem cell transplantation, intensified conditioning is more likely to be associated with the increase of severe GVHD triggered by mucosal injury due to the adverse effect of drugs; such severe GVHD often results in mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The HO-1 rs2071746 SNP was analyzed in 593 HLA-A, -B, -C, -DRB1, -DQB1, and -DPB1 allele-matched, unrelated BMT donor-transplant recipient pairs (Table 1). Based on the disease status and other risk factors that influence post-transplant outcomes, as previously reported [22,[27][28][29], standard-risk disease was defined as acute myeloid leukemia (AML), acute lymphoblastic leukemia (ALL), or multiple myeloma (MM) in the first complete remission; malignant lymphoma (ML) in any complete remission; or myelodysplastic syndrome (MDS) or chronic myeloid leukemia (CML) in the chronic phase. Both ALL and AML, which were in the second complete remission, were included in the high-risk group, according to recent reports [27,29] indicating that patients with AML and ALL in the second complete remission have worse post-transplant outcomes than those in the first complete remission.…”
Section: The Frequencies Of Ho-1 Genotypesmentioning
confidence: 99%